Pavement Crack Detection and Classification Using Deep Learning Techniques - T. Pooja; G.V.S. Ananthnath (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Accurate detection and analysis of pavement cracks are essential components of intelligent road maintenance systems. The primary challenges in this area stem from the irregular shapes, complex topologies, and texture-like noise often associated with cracks. To address these issues, this study introduces a comprehensive and robust automated framework capable of identifying crack types and evaluating their severity levels. A specialized crack detection network is designed, incorporating a multi-scale dilated convolution module to effectively extract contextual information about cracks. An attention mechanism is integrated to enhance the refinement of high-level features. These enriched features are then fused through an upsampling module, enabling the generation of detailed detection outputs. Following detection, a novel classification approach is applied to categorize the cracks into four types—transverse, longitudinal, block, and alligator. Additionally, the severity of the cracks is quantified by measuring the average width and spacing between crack branches. This integrated system offers an effective solution for real-time pavement assessment and management.
Keywords: Pavement crack analysis; crack categorization; deep learning; ResNet; attention mechanism